PENGARUH PENGGUNAAN VIDEO PEMBELAJARAN TERHADAP MOTIVASI BELAJAR SISWA KELAS IV SD - Ferdiansyah; Haifaturrahmah; Syafrudin Muhdar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The use of instructional videos has become an innovation in education to increase student learning motivation, particularly at the elementary school level. This study aims to examine the effect of using instructional videos on the learning motivation of fourth-grade elementary school students. Based on a literature review and empirical studies, it was found that instructional videos have a significant positive impact on learning motivation. This medium can increase student enthusiasm, engagement, and curiosity through interactive and visual presentation of material. Empirical research shows an increase in motivation scores from pretest to posttest after video implementation, supported by theories such as Edgar Dale's Cone of Experience and multimedia learning theory. However, video effectiveness depends on production quality, duration, and integration with the curriculum. Challenges such as limited access to technology in certain areas also need to be addressed. The results of this study recommend the use of instructional videos as an effective strategy to increase the learning motivation of fourth-grade elementary school students, with suggestions for further research to explore optimal video types and their long-term impact on academic achievement. Keywords: Instructional Videos, Learning Motivation, Fourth-Grade Elementary School Students, Instructional Media, Educational Technology.